Control of Virtual Synchronous Generator for Frequency Regulation Using a Coordinated Self-adaptive Method - Hongwei Fang; Zhiwei Yu (CSEE Journal of Power and Energy Systems, 2024)
Power inverter adopting virtual synchronous generator (VSG) control can provide inertia support for distributed generation systems. However, it cannot take into account the dynamic regulation characteristics of frequency. Thus, when the system encounters a sudden change in load or disturbance, the dynamic process of frequency regulation will be greatly influenced. In view of this issue, an improved VSG control strategy based on a coordinated self-adaptive (CSA) method is proposed. The time domain analysis method is used to study the influences of virtual inertia and damping parameter perturbation on the system steady and dynamic performances. Furthermore, in order to make the control strategy suitable for large load changes and suppress frequency variations beyond the limit, the secondary frequency modulation is introduced into the control loop. Through the coordinated adaptive control of virtual inertia, virtual damping and frequency modulation, the dynamic performance of VSG frequency regulation can be obviously improved. Simulation and experiment results have verified the effectiveness of the proposed CSA control strategy.